Reforming Marriage Law in Indonesia: A Critical Examination of Islamic Law on the Ban of Interfaith Marriages - Setiawan, Iwan; Arifin, Tajul; Saepullah, Usep; Safei, Abdulah (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
Interfaith marriage is a widely debated issue in Indonesia, particularly within the context of Islamic law. The prohibition of interfaith marriages has frequently been the subject of substantial criticism from an Islamic legal perspective. This article aims to critically examine the enforcement of this prohibition within Indonesia's marriage legal system. Employing a normative legal approach and literature analysis, the research explores various Islamic law perspectives on the prohibition of interfaith marriages. Additionally, this study analyzes the social, cultural, and legal impacts of this prohibition on Indonesian society. The findings indicate that the prohibition of interfaith marriages often conflicts with principles of justice, religious freedom, and human rights. In the context of Islamic law, several scholars and legal experts advocate for a more inclusive interpretation, emphasizing the importance of considering social context and justice in marital regulations. It is essential to formalize Islamic law by incorporating sociological and cultural aspects and aligning it with the national constitution. Therefore, the development of Indonesia's marriage legal system must consider universal values that evolve sociologically and culturally. In conclusion, this research underscores the need for reform in Indonesia's marriage legal system to accommodate individual needs and rights while respecting religious and cultural values. These changes are expected to provide legal recognition for interfaith marriages and promote a more inclusive and harmonious society.